HYDROCRACKING OF FISCHER-TROPSCH PRODUCTS - Teles, U. M.; Fernandes, Fabiano A. N. (Revista de Engenharia Térmica, 2007)
The hydrocracking behavior the product of a Fischer-Tropsch synthesis consisting of a C4–C30 mixture of paraffins and olefins on a platinum/amorphous silica–alumina catalyst has been analyzed and optimized. The influence of temperature on the selectiveness of the hydrocracking has been investigated. Time and temperature optimization was performed in order to obtain the best operating conditions for the enhancement of gasoline and diesel cuts.